HUKUM ABORSI MENURUT IMAM AL-GHAZALI DAN YUSUF AL-QARDHAWI - Siti Nur Rahmah; Anwar Hafidzi; Arie Sulistyoko (Fakultas Syariah UIN Antasari, 2018)
Abstract: Clear regulation is needed regarding the arrangement in term of Opinions on abortion have various views from many scholars as well as the law of abortion itself, because abortion is a controversy among scholars and society. From the opinions of Imam Al-Ghazhali and Yusuf Al-Qardhawi about abortion, it can be used as a reference for knowledge to address contemporary problems, such as this abortion. In the opinion of Imam Al-Ghazhali, he emphasized that abortion is absolutely forbidden and accepts the Ijab and Qobul Akad at the time of conception. Then according to Yusuf Al-Qardhawi's view regarding the law of permissible abortion, because in his opinion, he put forward the maslahah side to the soul of the conception itself, namely Mother, he accepts this with the existence of equality of legal causes.Abstrak: Pendapat terhadap aborsi memiliki berbagai pandangan dari banyak ulama begitupun hukum dari aborsi itu sendiri, sebab aborsi merupakan kontroversi dari kalangan ulama dan masyarakat. Dari pendapat imam Al-ghazhali dan Yusuf Al-Qardhawi tentang aborsi dapat dijadikan bahan rujukan pengetahuan untuk menyikapi masalah masalah kontemporer, seperti aborsi ini. Dalam pendapat Imam Al-ghazhali, beliau menekankan aborsi adalah mengharamkan secara mutlak dan mengqiyaskan dengan Akad Ijab dan Qobul pada saat terjadinya pembuahan. Kemudian menurut pandangan Yusuf Al-Qardhawi mengenai hukum aborsi ialah memperbolehkan, sebab dalam pendapatnya, beliau mengedepankan adanya sisi maslahah bagi jiwa dari pengandung sendiri yaitu Ibu, beliau mengqiyaskan hal ini dengan adanya persamaan sebab hukum.